2014
DOI: 10.1007/s00256-014-1854-1
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular diffuse-type tenosynovial giant cell tumor of the deltoid muscle in a child

Abstract: Tenosynovial giant cell tumors (GCTs) typically form in the joints or extra-articular soft tissues such as the tendon sheath, and are benign tumors that commonly occur in the hands or wrists in the third to fifth decades of life. However, the diffuse type of extra-articular GCT arising within muscle is a rare soft tissue tumor, especially in a pediatric patient. In this report, we describe the magnetic resonance imaging and sonographic findings of a rare case of intramuscular diffuse-type GCT in the deltoid mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Six cases were located in a predominantly subcutaneous area, and five cases were entirely intramuscular. The intramuscular type tumor can affect any muscle, but most were located in the lower extremities, including thigh, buttock, and lower leg [ 4 ], which was similar to our case, while one case from another report [ 6 ] originated in an upper extremity, specifically the deltoid muscle.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Six cases were located in a predominantly subcutaneous area, and five cases were entirely intramuscular. The intramuscular type tumor can affect any muscle, but most were located in the lower extremities, including thigh, buttock, and lower leg [ 4 ], which was similar to our case, while one case from another report [ 6 ] originated in an upper extremity, specifically the deltoid muscle.…”
Section: Discussionsupporting
confidence: 76%
“…On cytogenetic study, this neoplasm was found to have clonal abnormalities, which are evidence for diffuse-type TSGCT. One report [ 6 ] suggested that the recurrence rate of intramuscular-type is lower than that of other types, as complete excision is easier for intramuscular masses than intra-articular lesions. However, the biologic behavior of intramuscular type tumors remains unclear due to the small number of cases, which necessitates further studies to determine the prognostic significance of intramuscular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, GCTTS is indeed a rare disease in the pediatric population. In Table 2 we summarised selected case reports published in the literature [2,13,[25][26][27][28][29][30][31][32].…”
Section: Pediatric Cases Of Gcttsmentioning
confidence: 99%
“…The reported intramuscular tenosynovial giant cell tumors are exclusively of the diffuse type. [3][4][5][6] Histologically, both types are composed of a mixture of mostly mononuclear cells, foamy macrophages, osteoclastic multinucleated giant cells and inflammatory cells in a background of hyalinized stroma. The histologic appearance of individual tumors may be quite variable, depending on the relative proportion of these cell types and the extent of stromal collagenization.…”
Section: Introductionmentioning
confidence: 99%